Homage to the last speakers of Halich Karaim - Csató, Éva Á. (Vilnius University Proceedings, 2024)
The article pays homage to the last fluent speakers of Halich Karaim. Two of them lived in the traditional settlement, the Karaim Street in Halich. A further speaker moved to Trakai and stayed there for the rest of her life with her sister. Thanks to favorable circumstances all of them could communicate in their daily life in Halich Karaim and maintain their full competence in their community language. Common to them all was their concern about the future of the language and their strong determination to transmit their linguistic competence to others, and especially to the younger Karaim generation.
Keywords: Turkic languages; Halich Karaim; language maintenance; language death; language documentation